Semantic Self-Regulation in Context of Teachers’ Experiences of Professional Identity Crisis - N. O. Sadovnikova; T. B. Sergeeva (Научный диалог)
The mechanisms of the semantic self-regulation in a situation of a teacher’s crisis of professional identity are discussed. In the theoretical analysis, particular attention is paid to the problems of regulation of behaviour in crisis situations. A review of studies on the role of axiological and conceptual entities of personality in difficult life and professional situations is made. The empirical study confirmed the hypothesis that a situation of experiencing a professional identity triggers the mechanisms of semantic self-regulation. It is shown that components of the regulation of teachers’ experience of professional identity crisis are interrelated with the parameters of the semantic sphere, in particular, with life guiding orientations, forming a complex, integrated mechanism. Central unit of semantic self-regulation is modelling, which is closely associated with life guiding orientations and stability of self-esteem of a teacher. It is suggested that modelling is a universal mechanism to deal with crisis situations, regardless of the peculiarities of professional orientation of a teacher. Mechanisms of semantic self-regulation showed a complex and ambiguous nature of the relationship with the peculiarities of professional experience of crisis, which suggests the presence of different types of semantic self-regulation and different strategies of crisis overcoming by teachers. This in turn suggests the novelty and heuristic value of the research results. The practical significance of the results is determined by the fact that they constitute the information basis for the development of individualized programs of psychological support of teachers in a situation of professional identity crisis.